2006
DOI: 10.1149/1.2150158
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation of n-Butane in a Solid Electrolyte Membrane Reactor

Abstract: The partial oxidation of n-butane to maleic anhydride ͑MA͒ in a solid electrolyte membrane reactor was studied in three different operation modes: electrochemical membrane reactor ͑EMR͒, cofeed membrane reactor ͑CR͒, and mixed-feed membrane reactor ͑MMR͒. The EMR operation exhibited lower selectivity to MA but higher conversion of oxygen than the CR operation. The electrochemical oxygen pumping in the MMR operation led to decrease in the MA selectivity compared to the CR operation. By means of comparing the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
(46 reference statements)
5
11
3
Order By: Relevance
“…The observed current increase with butane containing feed gas in the anodic feed could be explained by immediate oxidation reactions on the Au electrode which lowered the oxygen concentration. However, this observation is not in a direct agreement with the observation of Ye et al where only negligible reactions of butane were observed on the Au anode in the membrane reactor Au|YSZ|Pt-Ag [24]. It should be noticed here that the measurements by Ye et al were carried out under oxygen pumping mode (EOP), which is not directly comparable with our present study.…”
Section: The Influence Of the Catalyst To The Induced Currentcontrasting
confidence: 98%
See 3 more Smart Citations
“…The observed current increase with butane containing feed gas in the anodic feed could be explained by immediate oxidation reactions on the Au electrode which lowered the oxygen concentration. However, this observation is not in a direct agreement with the observation of Ye et al where only negligible reactions of butane were observed on the Au anode in the membrane reactor Au|YSZ|Pt-Ag [24]. It should be noticed here that the measurements by Ye et al were carried out under oxygen pumping mode (EOP), which is not directly comparable with our present study.…”
Section: The Influence Of the Catalyst To The Induced Currentcontrasting
confidence: 98%
“…York et al [6] investigated the electrochemical butane oxidation with an Au|YSZ|Ag cell. At reaction temperature of 723 K and an applied current of 4.5 mA, no MA was detected under electrochemical oxygen pumping conditions, which is in agreement with the observations of Ye et al [24] with Au|YSZ|Pt-Ag reactor at 753 K. Based on these literature reportings and our own results, we might conclude that the formation of MA is not occurring on the Au electrode surface.…”
Section: The Influence Of the Catalyst To The Induced Currentsupporting
confidence: 92%
See 2 more Smart Citations
“…In our EMR application, however, the catalyst is fixed on the electrolyte membrane in the anodic compartment, where the oxygen is supplied in a very low concentration. We have shown before [9,10,21,22], that under these conditions part of the transported oxygen ions is converted neither to MA nor to CO 2 or CO, but is recombined to gaseous dioxygen. Due to these parallel processes, the oxygen concentration in the anodic compartment can vary, which in turn might influence the conductivity.…”
Section: Influence Of the Oxygen Partial Pressurementioning
confidence: 89%